ANALISIS LITERATUR TENTANG MEDIA PEMBELAJARAN BERBASIS DIGITAL DALAM MENINGKATKAN EFEKTIVITAS BELAJAR MATEMATIKA - Prasetyo, Rizky Budi; Meiliasari, Meiliasari (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
This study analyzes the role of digital learning media in enhancing the effectiveness of mathematics learning using the Systematic Literature Review (SLR) method on 17 articles that meet the inclusion criteria: (1) published between 2018 and 2024, (2) containing empirical data on mathematics learning, and (3) discussing the use of digital media. Based on the selected and reviewed analysis, four types of digital learning media were identified: web-based media, applications and software, augmented reality (AR), and artificial intelligence (AI). Each type of media has its own characteristics and advantages that support the understanding of mathematical concepts in a more interactive and engaging way. The characteristics of effective learning media include interactivity, ease of access, visual appeal, and the ability to enhance students' interest and understanding. However, challenges such as infrastructure limitations, lack of teacher skills, and dependence on stable internet access hinder optimal implementation. Data analysis was conducted qualitatively and descriptively to identify factors that support and hinder the use of these media in mathematics education. In conclusion, digital learning media hold great potential to improve the quality of learning, provided they are supported by teacher training and adequate infrastructure development.